Application of Ru(edta) complexes in biomimetic activation of small molecules. Kinetic and mechanistic impact - Chatterjee, Debabrata; van Eldik, Rudi (Academic Press Inc., 2023)
Mechanistic understanding of enzymatic activation and transformation of small molecules to value added product(s), is a long-term challenge in biological and energy-related chemistry. In this chapter we assess our research contributions illustrating the prospects of the Ru(edta) complexes (edta4 − = ethylenediaminetetraacetate) as potential model for rational understanding the role of the metalloenzymes that efficiently catalyze the transformation of small molecules to value added product(s). The current research contributions compiled herein, reveal the enzyme mimicking ability of Ru(edta) complexes pertaining to the reduction of O2 to H2O2, reduction of CO2 to HCOOH, oxidation and S-nitrosylation of biological thiols, and cross-talk between NO and H2S. These processes are conversed in more details, highlighting the mechanistic aspects of the aforementioned reactions that occur in nature, and are catalyzed by active sites of metalloenzymes. An overview of the advancement in this research and prospect of such complexes in bio-mimetic activation of small molecules is presented herein.
CRIS-Team Scopus Importer:2023-03-10
Keywords: Activation of NO and NO; Biomimetic catalysis; Oxygen reduction reaction; Reduction of CO; Ru(edta) complexes; S-nitrosylation of thiols and cross talk between H; Small molecules activation